Дослідження періодичних розв'язків нелінійних автономних систем у критичному випадку - Король, І.І. (Український математичний журнал, 2008)
Исследуются условия существования и численно-аналитический метод приближенного построения периодических решений нелинейных автономных дифференциальных систем в критическом случае. We investigate existence conditions and a numerical-analytic method of the approximate construction of
the periodic solutions of nonlinear autonomous differential systems in a critical case.